THE METHODS OF DEVELOPING STUDENTS’ PROFESSIONAL MOBILITY IN THE PROCESS OF LEARNING FOREIGN LANGUAGES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Current examination of the student's readiness for professional mobility should be carried out based on the following set of methods: test; questionnaire; analysis of the results of self-study work and practical assignments, conducting control work.